Enhancement of stability of Pd/AC deoxygenation catalyst for hydrothermal production of green diesel fuel from waste cooking oil. (6th April 2022) - Mohammed, Sahar T.; Hamad, Khaleel I.; Gheni, Saba A.; Aqar, Dhia Y.; Ahmed, Safaa M.R.; Mahmood, Marwan A.; Ceylan, Selim; Abdullah, Ghassan H.
Highlights: Highly active Pd/AC catalysts from agro-waste for deoxygenation of waste cooking oil. Microporous structure with acidic sites to enhance deoxygenation. Protective coating layer alters the deactivation reaction of the deoxygenation catalyst. The coating layer did not influence the kinetics of deoxygenation reaction. Abstract: Nowadays, one of the most challenging problems in the production of green diesel fuel from fats sources is the deactivation of the deoxygenation catalyst after a certain period of time. The structure of the catalyst is damaged due to several problems and the performance is degrading over time. In this work, a high stability deoxygenation catalyst was prepared from agricultural waste and used for hydrothermal production of green diesel fuel from waste cooking oil. The support of the catalyst was prepared using apricot seeds. Palladium (Pd) was loaded by the incipient wetness impregnation method. The Pd/AC substrate was coated by a nanofilm aluminum protective layer using the sol–gel method to prevent rapid deactivation of the catalyst, prolong the catalyst lifetime and enhance the stability. The characterization tests showed good thermal stability, a uniform coating around the Pd/AC substrate, and a high surface area of 726.9 m 2 /g of the coated catalyst. Micropores increase the activity of oleic acid deoxygenation from attributed to improved acid site accessibility within the fluffy Pd/AC substrate. Kinetic experiments were carried out in a hydrothermal autoclave reactor under an inert atmosphere (N2 ) over the coated and the uncoated catalyst at a temperature range of 300–350 °C, pressure range 30–50 bar and residence time up to 3 h. The results showed that the catalytic deoxygenation of the oleic acid is a first-order reaction. The rate of deactivation of Pd/AC deoxygenation catalyst was determined at 350 °C and 50 bar in a hydrothermal autoclave reactor. The results showed that deactivation reaction of the Pd/AC catalysts followed first-order kinetics and occurred by the poisoning mechanism. The deactivation reaction was significantly altered due to coating of deoxygenation catalyst and elevating of the activation energy of the deactivation reaction.